Food traceability model using blockchain technology - Rudy Tjahyadi; Meyliana Meyliana; Harco Leslie Spits Warnars; Richard Wiputra (Institute of Advanced Engineering and Science, 2026)
The complexity and globalisation of food supply chains raises concerns over food safety, authenticity and provenance. Data fragmentation, fraud and lack of transparency mean traditional traceability solutions are often ineffective and diminish consumer confidence. Blockchain technology can solve these limitations as it is decentralized, transparent and immutable. This study shows that blockchain technology has the potential to change the food traceability landscape by allowing food products to be securely and verifiably traced from raw ingredients to consumers. We discuss how such a system can improve openness, immutability, and information integrity. We will discuss the issues of scalability, interoperability, data security and stakeholder collaboration in the food sector in the implementation and adoption of blockchain. Preferred reporting items for systematic reviews and meta-analyses (PRISMA) and design science research (DSR) methods were used to develop a blockchain-based food traceability model, ChickenTrax, from 33 papers from 2020 to 2025. Its goal is to enable real-world deployment within the poultry sector and to improve the knowledge of the advantages and limitations of the use of the blockchain technology for a more robust and reliable food traceability system (FSTS).